Pengaruh Financial Knowledge, Penggunaaan Fintech dan Inovasi Produk terhadap Kinerja Keuangan Pelaku UMKM di Kecamatan Kerjo - Fredana Bintang Winarsa; Sumaryanto Sumaryanto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
The purpose of this study is to examine how financial knowledge, the use of financial technology (fintech), and product innovation influence the performance of micro, small, and medium enterprises (MSMEs). This research employs a quantitative method with an associative approach. A purposive sampling technique was applied to select 100 MSME actors in Sukoharjo Regency as the respondents. Data were collected through questionnaires and analyzed using multiple linear regression.The results reveal that financial knowledge, fintech utilization, and product innovation have a positive and significant effect on MSME performance. These findings highlight the importance of improving financial literacy, leveraging financial technology, and enhancing product innovation as strategic efforts to strengthen competitiveness and improve the performance of MSME.